ESTUDO DA UTILIZAÇÃO DOS NANOTUBOS DE CARBONO NA REMOÇÃO E DETECÇÃO DE DEFENSIVOS AGRÍCOLAS: UM ESTUDO DE PRIMEIROS PRINCÍPIOS - Tonetto, Bruno Costa (2018)
We studied the structural and electronic properties of paraquat, glyphosate, aminomethylphosphonic acid, methylamine and formaldehyde molecules interacting with carbon nanotubes in pristine form and carboxylated, through computer simulations based on Density Functional Theory (DFT). Carbon nanotubes (CNTs) is emerging as a material that presents a series of specific properties, making these compounds as promising systems for a variety applications. Among these, we highlight use carbon nanotubes as filters or sensors of toxic molecules. In this work, the objective is to use carbon nanotubes to removal or detection paraquat, glyphosate and its derivatives of food and environment. Our results showed the interaction between these molecules and the carbon nanotubes does not change the properties of these herbicides, with binding energies ranging from 0.12 eV to 0.82 eV. For the carboxylated carbon nanotubes obtained binding energies from 0.33eV to 1.41eV. Therefore, these values indicate that carboxylated nanotubes are not suitable for sensing and filtering because the high energy cost required for the eventual removal of these molecules of the tubes. Failure to change the molecules in the presence of carbon nanotubes is desired for future experimental application of carbon nanotubes as a sensor or filter of these pollutants, ie, our results suggest that either a filter based nanotubes can be reused several times to removal these molecules, as well as molecules after they are removed from the presence of nanotubes can be reused in agriculture again.